Efficiency Drivers of MFIs : The Role of Age - Kneiding, Christoph; Mas, Ignacio (World Bank, Washington, DC, 2012)
Microfinance institutions (MFIs) are becoming more efficient. This brief sheds light on how the age of individual MFIs and the age of the industry affect efficiency improvements. On an MFI level the authors look into scale economies, cost structure, and process durations as potential efficiency drivers. On an industry level the authors look into knowledge spillovers from one MFI to the other and market wide learning effects.